Wastewater treatment : advanced processes and technologies - Rao, D. G. (CRC Press, 2012)
Emphasizing new technologies that produce clean water and energy from the wastewater treatment process, this book presents recent advancements in wastewater treatment by various technologies such as chemical methods, biochemical methods, membrane separation techniques, and nanotechnology. It addresses sustainable water reclamation, biomembrane treatment processes, advanced oxidation processes, and applications of nanotechnology for wastewater treatment. It also includes integrated cost-based design methodologies. Equations, figures, photographs and tables are included within the chapters to ai.
Keywords: Sewage -- Purification.; elektronické knihy; electronic books